PHYLOGENY OF Glyphodes Guenee (Lepidoptera: Crambidae: Spilomelinae) BASED ON NUCLEOTIDE SEQUENCE VARIATION IN A MITOCHONDRIAL CO I GENE: CONGRUENCE WITH MORPHOLOGICAL DATA - Hari Sutrisno Sutrisno (BRIN Publishing (Penerbit BRIN), 2003)
The phylogeny of Glyphodes Cuenee (14 species) and four outgroup species (Feltia jaculifera, Metallarcha aureodiscalis, Talanga sexpunctalis and Agrioghrypta eurytusalis) was inferred fromnucleotide sequence variation across a 686-bp region in the CO I gene. Over the entire 686-bp region, 19.9% sites were informative (3.35% in the 1st-, 0.29% in the 2nd - and 16.32% in 3rd - codon position). The results also showed that the base composition of this region was high A+T biased (C= 0.258) and the averages ofestimated sequence divergence in the comparisons between species within and between groups were 7.1% and 9.0%, respectively. In general, the phylogeny based on CO I gene by including all substitutions or any partial data set used in this study was not only able to recover almost the three monophyletic groups withinGlyphodes as previously recovered by morphological phylogeny but also showed more clearly the relationships among them: Glyphodes group 2 was branched off first then followed by group 3 and 1.